PTU-104 Small Bowel Transplantation Does Improve Quality of Life, But Needs A Disease Specific Tool. (17th August 2016) - Blackwell, V; Holdaway, L; Travis, S; Reddy, S; Vrakas, G; Smith, A; Vaidya, A; Friend, P; Allan, P
Abstract : Introduction: Small bowel intestinal transplantation is provided for patients with intestinal failure for whom complications, among other reasons, such as intestinal failure associated liver disease (IFALD), multiple central venous catheter (CVC) infections, loss of venous access or who have intra-abdominal desmoids. In addition, within the American guidelines is quality of life (QoL). There is no robust QoL data collection tool to compared patients undergoing small bowel transplantation compared to those remaining on parenteral nutrition (PN). Methods: Data of all patients undergoing small bowel transplant in Oxford, one of the 2 national adult small bowel transplant centres in the UK, are captured on a prospectively entered database. QoL data was recorded using patient related outcome measures (PROM) and using EQ5D both pre and post intestinal transplant. Data was audited in January 2016. The Oxford Intestinal Failure (IF) cohort also had QoL data recorded and was used as a comparator. Results: PROM measurements include survival where out of 29 transplants that had occurred, 19 were alive (66%), 1 (5%) was on TPN as an inpatient and 2 (11%) were on home iv fluids, 16 (84%) were on no TPN, iv fluids or tube enteral nutrition support. Questionnaire data utilised the visual analogue scale part of the EQ5D as a global rating scale for the patients to record their assessment of QoL. It was recorded as median (range) for 4 patients who completed questionnaires pre and post transplant giving 4 pre results and 7 post results; pre-transplant 17.5 (10–30) and post-transplant 79.5 (60–85). 4 patients had only filled in pre-transplant questionnaires: 35 (10–50), which included 1 patient who died post-transplant, 2 patients at their assessment and 1 who was post-explant of their graft for chronic rejection and are listed for retransplantation. In addition, 5 patients completed post-transplant questionnaires on 7 occasions 80 (55–90). This compares to the Oxford IF cohort of whom 30 patients filled in a questionnaire on 1 occasion, 15 on a 2 nd at a median of 5 months (1–15) following the first and 3 on a 3 rd occasion at 4 months (3–5) after the second. The median (range) for the Oxford IF cohort was 62.5 (25–100), 65 (30–100), 75 (60–85). Conclusion: From this preliminary series, small bowel transplantation does improve quality of life post-transplant compared to pre-transplant. The level post-transplant is better than that experienced by patients on home PN. A better QoL data tool is required to effectively assess patients undergoing small bowel intestinal transplantation that can be effectively compared to patients who remain on PN. Disclosure of Interest: V. Blackwell: None Declared, L. Holdaway: None Declared, S. Travis: None Declared, S. Reddy: None Declared, G. Vrakas: None Declared, A. Smith: None Declared, A. Vaidya: None Declared, P. Friend: None Declared, P. Allan Consultant for: Abbvie, Conflict with: BresMed advisor; NPS Pharma educational grant